A case study of the efficiency of the space plan and furniture layout of an office - Estur, James Andrew L.; Quevedo Ma. Teresa P. (2009.)
The study sought to assess the efficiency of the space plan and furniture layout of an office located in a university in Metro Manila. It aimed to find out whether the plan and layout addressed the needs and concerns of the management and staff. Efficiency was assessed in terms of space utilization, location and clustering of workstations/desks, circulation, communication, movement, and mobility and access. Survey questionnaires were handed out to fifteen employees of the office. The division leaders, as well as the section head, were interviewed regarding their office needs and concerns. Observation determined the effects of the space plan and furniture layout on the activities of the management and staff. Lastly, the office space was documented to obtain critical measurements and details. Results revealed that employees engaged in a variety of work related activities, which were mostly performed inside the workstations. The staff also frequently collaborated with co-workers or attended to inquiries at the service windows. In regard to space utilization, the main problem was the disproportionate and expanded use of space. A major problem in this area was the lack of storage. The existing office layout yielded problems such as unsatisfactory location of the areas/divisions in relation to workflow and disorganized orientation of workstations. Circulation paths did not adhere to standards and were therefore insufficient. Obstructions further reduced mobility along the circulation paths. Access to the workstations/desks and to other areas in the office was inadequate. In terms of communication, the open plan afforded conducive intra-office communication although communication devices (i.e. telephone) were sufficient. The following solutions are recommended to improve efficiency in the office. Sufficient space should be allocated for each area, division, or workstation to avoid congestion and crowding. In particular, there should be enough space for storage and bigger workstations. The layout should be able to sustain the workflow of the office through better planning of the areas, divisions, and workstations. Circulation paths should adhere to standards specifically in terms of widths and placement. Access can be improved by widening clearances to workstations/desks and other areas. Finally, long distance communication should be enhanced by increasing the number of telephones in the office and locating them in ideal areas.
Thesis (BS Interior Design)--University of the Philippines Diliman
Keywords: Office layout